The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40641-015-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Storm Surge Risk

Abstract: Tropical cyclone storm surge represents a significant threat to communities around the world. These surge characteristics vary spatially and temporally over a range of scales; therefore, conceptual frameworks for understanding and mitigating them must be cast within a context of risk that covers the complete range of hazards, their consequences, and methods for mitigation. A review of primary overlapping time scales and associated spatial scales for tropical cyclone surge hazards covers two scales of particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…A good example of a location that restricts overwater approach angles can be found in the New York Bight. Figure 7 from Resio and Irish (2015) shows there is a strong relationship between heading and storm intensity in the historical sample of storms in this area. This type of correlation increases the likelihood of intense storms making landfall in the New York Bight, which then affects surge probabilities.…”
Section: Variations In the Quantification Of Uncertaintymentioning
confidence: 92%
See 1 more Smart Citation
“…A good example of a location that restricts overwater approach angles can be found in the New York Bight. Figure 7 from Resio and Irish (2015) shows there is a strong relationship between heading and storm intensity in the historical sample of storms in this area. This type of correlation increases the likelihood of intense storms making landfall in the New York Bight, which then affects surge probabilities.…”
Section: Variations In the Quantification Of Uncertaintymentioning
confidence: 92%
“…This complicates the need to quantify the epistemic uncertainty (the state-of-the-art modeling biases and random errors) related to interrelationships among all the forcing factors neglected in an idealized model that simulates synthetic storms, such as hurricane-land interaction which can be critical at landfall and complex multivariate correlation structures. A factor of particular importance is the neglect of baroclinic energy sources in the overall energy balance, as noted in the review by Resio and Irish (2015). Hurricane Sandy was transitioning into an extratropical system when it approached landfall, drawing about 50% of its energy from baroclinic sources.…”
Section: Potential Problems With Transitioning Extratropical Stormsmentioning
confidence: 99%
“…Several papers have attempted to establish some level of understanding of the relative errors in differing models (Leuttich et al 2013;Kerr et al 2013;Resio and Irish 2015); however, as will be shown here, it is important to understand errors in storm surges relative to the errors in forecast hurricane characteristics. It is hoped that this paper will help provide the scientific and engineering community with at least a preliminary estimate of the implications of surge modeling accuracy for forecast decision-making.…”
Section: Existing Methodsmentioning
confidence: 99%
“…8 Comparison of the primary surge at the Battery estimated from the SLOSH and ADCIRC models for the nine highest surge generating storms hindcast by Lin et al (2010) constrained models (Leuttich et al 2013;Kerr et al 2013). As pointed out in Resio and Irish (2015), the winds in SLOSH used in Fig. 8 may not represent a true estimate of the bias of this model, since other studies, using winds specifically intended for SLOSH applications, have indicated that the SLOSH model does not produce a bias of this magnitude in general.…”
Section: Estimation Of Surge Uncertainty In Forecasts Due To Surge Momentioning
confidence: 97%
“…Resio and Irish, 2015;Needham and Keim, 2014;Keim et al, 2007;Elsner et al, 1999;Simpson and Lawrence, 1971), wave conditions related to a storm event can be observed along distant coasts, well beyond the region of wind stress. Hence, a modification in storm characteristics will be associated with inherent changes in wave height and the storm surge reaching the coastline, which are the two main factors responsible for considerable economic losses in coastal and offshore areas (Mendelsohn et al, 2012;Neumann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%